Morphology‐Controlled Molybdenum Disulfide/Candle Soot Carbon Composite for High‐Performance Supercapacitor. Issue 22 (18th June 2020) - Sangabathula, Omkar; Potphode, Darshna; Sharma, Chandra S.
Abstract: Facile assembly of robust electrodes with excellent electrochemical performances is still challenging yet consequential for supercapacitor applications. Although molybdenum disulfide (MoS2 ) has versatile properties, restacking of molybdenum layers and poor intrinsic conductivity restrict to explore it for electrochemical applications. Herein to address these challenges, we utilized candle soot derived carbon to fabricate MoS2 /Carbon (C) nanocomposite through a simple hydrothermal synthesis method. The prepared composite delivered specific capacitance of 452.7 Fg −1 at a current density of 1 Ag −1 in 3 M KOH electrolyte and profound capacity retention and coulombic efficiency of 94.8% and 93.7% after 10, 000 charge‐discharge cycles respectively. Furthermore, we fabricated asymmetric supercapacitor device using MoS2 /C as the positive electrode and candle soot derived carbon as a negative electrode (MoS2 /C // C) which showed excellent energy and power density values with an impressive capacitance retention of 100% over 10, 000 cycles. The exceptional electrochemical performance of MoS2 /Carbon composite thus indicates the potential application for high‐performance supercapacitor devices. Abstract : In the present work, we have orchestrated 3D flower morphology of MoS2 and MoS2 /C composites for Supercapacitor applications. As prepared MoS2 /C (1 : 1) composite delivered a specific capacitance of 453 Fg −1 at a current density of 1 Ag −1 in 3 M KOH electrolyte with profound coulombic efficiency of 93.7% after 10, 000 charge‐discharge cycles. Whereas the fabricated asymmetric supercapacitor device shows excellent energy and power density values with an impressive capacity and capacitance retention of 100% over 10, 000 cycles.